The measurement of the p-i-n diodes parameters in the fin-line in the millimeter wave region (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2018)
Introduction. It is known, that it is desirable to measure the parameters of semiconductor elements in the transmission lines, in which they are supposed to be installed. The existing methods of measuring them need for calibration procedure, connected with finding the reference plane – a laborious procedure in some cases is generally not feasible with necessary accuracy. In particular, this applies to the requirements in the fin-line which is convenient electrodynamic medium for realization of hybrid-integrated circuits (GIS) in the millimeter wave region. In this paper we propose a technique for measuring the parameters of diodes that does not require calibration. The proposed method makes it possible to find the complex conductivity of mixing, detector and p-i-n diodes (latter being open and closed) with reasonable accuracy.Description of measurement procedure. The measurement set-up contains a microwave generator, directional coupler for the reflected wave, a section of measuring fin-line with the diode to be tested and standard waveguide short. As a result of theoretical analysis it was shown, that in the case of insignificant losses in measuring section the procedure for finding the diode parameters can be reduced to measurements of distances between the positions of short, at which the maximum and minimum of reflected wave are observed.Discussion. This section contains the estimation of errors inherent to the proposed method. It was shown, that with the real losses in measuring section the errors in the determining of the diode parameters do not exceed 20% that can be considered acceptable for the development of circuits containing these diodes. As an argument, the fact, that proposed method does not require procedure for establishing the reference plane, inherent to standard methods of measuring impedance, and being the source of the main measurement errors, is put forward.Conclusion. The proposed technique allows us to quickly estimate the parameters of the diode. In this case the measurements are made in the electrodynamic system of GIS developed with these diodes that gives adequate results for its development. The measurement errors are not more than 20% and can be reduced by reducing the losses in the measuring section.